Kinetics and process optimization studies for the effective removal of cresyl fast violet dye using reusable nanosized mullite - Omar A. Fouad; Yara M. Adly; Wafaa M. Hosny; Gehad G. Mohamed; Maysa R. Mostafa (Scientific Reports)
Abstract The swift rise of hazardous dye effluent from diverse sectors continues to be a severe public health problem and a top priority for environmental preservation, presenting a significant obstacle to the current conventional water treatment systems. This study aims to develop an efficient and reusable approach for removing cresyl fast violet dye using mullite nanoparticles. Some factors such as pH, nano-mullite dosage, agitation speed, time, and others that affect the removal process were studied. The mullite nanoparticles’ shape, particle size, pore diameters, and crystal phase structure are characterized using many techniques such as Brunauer-Emmett-Teller (BET) surface area, X-ray diffraction (XRD), transmission electron microscopy (TEM), Contact angle, Zeta potential, scanning electron microscope (SEM) as well as energy dispersive X-ray analysis (EDX). The optimal conditions were pH 7 and 600 rpm for 30 min at room temperature. Using statistical programs such as ANOVA and Design Expert, the dye removal parameters were modeled and optimized, where the removal percentage was about 99%. In addition, the experimental elimination process exceeded 90% after just 10 min. Langmuir, Freundlich, Dubinin-Kaganer-Raduskevich (DKR), and Temkin isotherm equations were examined to find the adsorption isotherm. The experimental data fits the pseudo-second-order model and the Freundlich isotherm. Thermodynamic investigations confirmed that the adsorption process was endothermic and spontaneous. The nano-mullite was employed for the removal process, and its recycling ability supports its economic benefits. It was found that the high percentage of elimination remained consistent for more than 3 cycles.